ANALISIS EFEKTIVITAS BIAYA METODE KONTRASEPSI PIL DAN SUNTIK UNTUK AKSEPTOR KB MANDIRI DI PUSKESMAS TONJONG - Ratu Fiqi Hanun; Aziez Ismunandar; Luthfi Hidayat Maulana (Prodi Farmasi Fakultas Sains dan Teknologi Universitas Peradaban, 2021)
Based on data from BKKBN in 2015 it is known that the results of contraceptive services in Indonesia in 2012 using injection method contraception 30,649 participants (49.70%), pills 12,068 participants (19.57%), IUD 8,200 participants (13.30%), implants 6,408 participants (10.39%), MOW 2,009 (3.26%), condoms 2,264 participants (3,67%) and MOP 75 participants (0.12%). This will certainly affect the budget of the funds used. The cost-effectiveness analysis of the use of contraceptive methods is carried out to find out which method of contraception is the most cost-effective for society. The purpose of this study is to find out the most cost-effective contraceptive method between pills and injection for independent birth control acceptance at Tonjong Public Health Center. Data retrieval using the patient's medical records and prices on the Pharmaceutical Installation. The population in this study was all birth control patients in Pukesmas Tonjong during July-December 2019. Sampling method with total sampling so that it is obtained by 31 people. This research is a quantitative descriptive study with a cross-sectional research design. The data analysis used in univariate analysis and Cost-Effectiveness Analysis. Based on the results of the study can be concluded that the most cost-effectiveness analysis method based on the value of ACER and ICER, which has the most effective cost that is pills, the smaller the value of ACER a drug then the more cost-effective the drug. The contraceptive pill is in quadrant II which offers high effectiveness and low cost.